AN ANALYSIS OF ILLOCUTIONARY ACTS IN PODCAST RUANG SANDI VIDEOS BY SANDIAGA UNO - Risa Dui Sitorus; Rotua Elfrida (Journal of Applied Linguistics, 2022)
This study aims to find the types of illocutionary acts and the most dominant types of illocutionary acts of illocutionary used by Sandiaga Uno. The source of data of this study was taken from 4 videos that uploaded in Youtube Channel Podcast Ruang Sandi from March-April 2021. And this study only focuses on the illocutionary acts used by Sandiaga Uno. The writer uses a qualitative descriptive method to describe the illocutionary acts by using the theory proposed by Searle in Rahayu (2018:177). After analyzing, the writer found 5 types of illocutionary acts used by Sandiaga Uno in the 4 videos, namely Assertives 33,8%, Directives 29,5%, Commisives 8,4%, Expressives 21,1%, Declaratives 7,04%. Based on the percentage, the most dominant used or the most frequently appeared is Assertives 33,8%. And the types of illocutionary acts assertives used by Sandiaga Uno to informing, describing, and asking to do something and telling the truth about something. Keywords : Pragmatics, Illocutionary Acts, Sandiaga Uno